2007
DOI: 10.1055/s-2007-964899
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cx43 and Angiogenesis in Exercised Mouse Hearts

Abstract: Several studies focused on the macroscopic architecture of increased cardiac wall induced by exercise training. Our goal was to evaluate myocardiocyte, interstitial and vascular component, and connexin-43 expression in endurance-trained mouse hearts. Sixty-three 10-week-old male Swiss mice were divided into four sedentary groups (C0, C15, C30 and C45) and three groups exercised respectively for 15 (T15-D; running intensity [RI]: 3.18 m/min; running duration [RD]: 75 min/first week and 150 min/second week), 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
6
31
0
Order By: Relevance
“…And a higher Cx43 protein level was found in the group LEP + EE than in the group EE. Bellafiore et al also reported similar results, and they found there is a progressive increase of Cx43 expression levels in response to endurance training that reached a peak in ventricular myocardium of mice exercised for 30 d [19].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…And a higher Cx43 protein level was found in the group LEP + EE than in the group EE. Bellafiore et al also reported similar results, and they found there is a progressive increase of Cx43 expression levels in response to endurance training that reached a peak in ventricular myocardium of mice exercised for 30 d [19].…”
Section: Discussionsupporting
confidence: 56%
“…Considering the same powerful cardioprotective effects of both EP and IP as well as the key role of increased expression of Cx43 in IP cardioprotection, we hypothesized that Cx43 may involve in cardioprotective signaling transduction of EP. It has been observed that endurance exercise training preserves a higher expression level of Cx43 in heart under resting conditions [19] . Moreover, the expression level of Cx43 is down-regulated in trained mice during acute exercise [20].…”
Section: Introductionmentioning
confidence: 99%
“…Kostin and colleagues (26) showed that the upregulation of Cx43 was detected in compensated (EF Ͼ 50%) cardiac hypertrophy. An increase in Cx43 expression was also found in exercise-trained mouse hypertrophied hearts (9). On the other hand, a decrease in Cx43 was detected in decompensated (EF Ͻ 30%) hypertrophied hearts, a result similar to those detected in heart failure patients (16,34,42).…”
Section: Discussionmentioning
confidence: 62%
“…Concerning to the role of tissue repairing by β-TCP, it has been reported that Cx43 has a novel role in modulating wound healing in fibrotic scar tissue and plays a role in the regeneration of cardiac muscle after tissue injury 21) . Interestingly, microvascular remodeling was associated with Cx43 upregulation 22) . Moreover, Cx43 deficiency in mice causes the dysregulation of coronary vasculogenesis.…”
Section: Discussionmentioning
confidence: 99%